Chairside Fabrication of an All-Ceramic Partial Crown Using a Zirconia-Reinforced Lithium Silicate Ceramic - Sven Rinke; Anne-Kathrin Pabel; Matthias Rödiger; Dirk Ziebolz (Hindawi Limited, 2016)
The chairside fabrication of a monolithic partial crown using a zirconia-reinforced lithium silicate (ZLS) ceramic is described. The fully digitized model-free workflow in a dental practice is possible due to the use of a powder-free intraoral scanner and the computer-aided design/computer-assisted manufacturing (CAD/CAM) of the restorations. The innovative ZLS material offers a singular combination of fracture strength (>370 Mpa), optimum polishing characteristics, and excellent optical properties. Therefore, this ceramic is an interesting alternative material for monolithic restorations produced in a digital workflow.